2014
DOI: 10.3109/02688697.2014.957648
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar Aspergillus osteomyelitis mimicking pyogenic osteomyelitis in an immunocompetent adult

Abstract: Spinal Aspergillus osteomyelitis is rare and occurs mostly in immunocompromised patients, but especially very rare in immunocompetent adult. This report presents a case of lumbar vertebral osteomyelitis in immunocompetent adult. A 53-year-old male who had no significant medical history was admitted due to complaints of back pain radiating to the flank for the last 3 months, followed by a progressive motor weakness of both lower limbs. Lumbar magnetic resonance imaging (MRI) demonstrated osteomyelitis and diski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 0 publications
1
11
0
3
Order By: Relevance
“…Here, we showed an immunocompetent patient who initially presented with pulmonary granulomatous lesions of undetermined origin and had vertebral osteomyelitis due to Aspergillus a few months later. Aspergillus osteomyelitis is frequently associated with immunosuppression such as organ transplantation, hematopoietic malignancies, diabetes mellitus, or other predisposing conditions [ 1 , 3 ], but it also develops in nonimmunocompromised patients [ 4 , 5 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we showed an immunocompetent patient who initially presented with pulmonary granulomatous lesions of undetermined origin and had vertebral osteomyelitis due to Aspergillus a few months later. Aspergillus osteomyelitis is frequently associated with immunosuppression such as organ transplantation, hematopoietic malignancies, diabetes mellitus, or other predisposing conditions [ 1 , 3 ], but it also develops in nonimmunocompromised patients [ 4 , 5 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, sometimes hyphae are hard to obtain from specimens, because the position and the size of sampling or the amount of bacteria contained in the relevant lesions might have an influence. In one case, hyphae were barely detected in 2 slides among over 100 slides [ 5 ]. Similarly, we failed to find hyphae in abundant lung specimens and could not clearly detect hyphae in lumbar lesions until the last surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In the current case series, 2 patients (2/6) had elevated WBC counts, all 6 patients (6/6) had elevated ESRs, and 4 patients (4/5) had elevated CRP. The imaging manifestations of Aspergillus spondylitis are related to the patient's immune function and course of disease [11,16]. X-ray and CT manifestations are often atypical.…”
Section: Discussionmentioning
confidence: 99%
“…1 Several authors reported difficulty in diagnosis of Aspergillus vertebral osteomyelitis in immunocompetent patients until open surgical biopsy or needle biopsy was performed. [8][9][10][11] Treatment of invasive aspergillosis with osteomyelitis should include antifungal therapy, correction of immunosuppression if possible, and surgical source control. There were fewer relapses in patients managed with surgery plus antifungal therapy in comparison with antifungal therapy alone.…”
Section: Reviewedmentioning
confidence: 99%